2021
DOI: 10.1039/d0ra09870a
|View full text |Cite
|
Sign up to set email alerts
|

Application of magnetic field to CO hydrogenation using a confined-space catalyst: effect on reactant gas diffusivity and reactivity

Abstract: Synergy between an external magnetic field and limited mass transfer within zeolite cavities leads to different diffusion abilities of CO and H2 during the reaction within the catalyst pores, leading to significant improvement in CO conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…This result was similar to a previous investigation into the FeCo/ZSM-5 catalyst. 49 The combined results from H 2 -TPR, XRD, XPS, and in situ XANES experiments evidently proved the evolution of the catalyst structure of the bimetallic NiFe system in comparison to the monometallic NiAl and FeAl catalysts for the hydrogenolysis of 5-HMF to the target 2,5-DMF product. The valence states of metallic Ni and Fe species were found to be major species aer hydrogen reduction, whereas the oxophilic NiO, Fe 3 O 4 , and FeO elements were detected as minor species for the bimetallic catalyst.…”
Section: Catalyst Characterizationmentioning
confidence: 75%
“…This result was similar to a previous investigation into the FeCo/ZSM-5 catalyst. 49 The combined results from H 2 -TPR, XRD, XPS, and in situ XANES experiments evidently proved the evolution of the catalyst structure of the bimetallic NiFe system in comparison to the monometallic NiAl and FeAl catalysts for the hydrogenolysis of 5-HMF to the target 2,5-DMF product. The valence states of metallic Ni and Fe species were found to be major species aer hydrogen reduction, whereas the oxophilic NiO, Fe 3 O 4 , and FeO elements were detected as minor species for the bimetallic catalyst.…”
Section: Catalyst Characterizationmentioning
confidence: 75%
“…Commonly used adsorbents for adsorbing organic waste gas are activated carbon particles, activated carbon fibers, molecular sieves, and adsorption resins. e advantages of adsorption technology are high removal rate, the removal rate can reach more than 95%, no secondary pollution, high purification efficiency, convenient operation, and automatic control [9].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides its thermal effect, the external magnetic field can conveniently control the distribution and structure of the catalyst bed in the reactor, thereby intervening in the physical/chemical adsorption of reactive species and the agglomeration of nanoparticles. Donphai et al 154 proposed that the introduction of a magnetic field can promote the diffusion of reactants in the gas−solid phase reaction. They observed that the effective diffusion coefficients of CO and H 2 in the catalyst pores were increased by 2.6 and 2.9 times, respectively, when an external magnetic field of 25.1 mT was applied during CO hydrogenation over a 5Fe−5Co/ZSM-5 catalyst.…”
Section: Conventional Thermal Catalysis Versus Nonconventional Catalysismentioning
confidence: 99%